Pin-based Enzymatic Electrochemical Sensing. (2017) - Rama, E. Costa; García, A. Costa; Fernández-Abedul, M.T.
Abstract: Already mass-produced stainless-steel pins offer the possibility of developing low-cost electroanalytical devices with a versatile disposition of the electrodes. Here we use these prefabricated pins as electrodes for enzymatic amperometric sensing. A conventional three-electrode configuration device is designed using two bare pins as reference and counter electrodes, and a carbon-coated pin as working electrode. Using a transparency sheet and standard connections as interface to conventional instrumentation, a pin-based sensor for glucose determination is developed. Finally, a multiplexed device with four pins acting as working electrodes, which can be useful for multiplexed immunosensing purposes, is designed.